2017
DOI: 10.1002/jaba.376
|View full text |Cite
|
Sign up to set email alerts
|

Noncontingent reinforcement for the treatment of severe problem behavior: An analysis of 27 consecutive applications

Abstract: Noncontingent reinforcement (NCR) is a commonly used treatment for severe problem behavior displayed by individuals with intellectual and developmental disabilities. The current study sought to extend the literature by reporting outcomes achieved with 27 consecutive applications of NCR as the primary treatment for severe problem behavior. All applications of NCR were included regardless of treatment outcome to minimize selection bias favoring successful cases. Participants ranged in age from 5 to 33 years. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 80 publications
(74 reference statements)
2
45
0
Order By: Relevance
“…Studies examining functional analysis outcomes by Iwata et al [65] and Hagopian et al [66] reporting on 154 and 176 consecutively encountered cases, respectively found the relative prevalence of functional classes of problem behavior to be comparable to that reported in the literature. Larger scale studies on functional communication training (n=21;n=58 [66,67]); noncontingent reinforcement ( [68],n=27); automatically reinforced SIB [48,49] produced findings comparable that reported across smaller scale studies in body of literature as a whole.…”
Section: Sib Types Features and Sub-types Main Referencessupporting
confidence: 63%
“…Studies examining functional analysis outcomes by Iwata et al [65] and Hagopian et al [66] reporting on 154 and 176 consecutively encountered cases, respectively found the relative prevalence of functional classes of problem behavior to be comparable to that reported in the literature. Larger scale studies on functional communication training (n=21;n=58 [66,67]); noncontingent reinforcement ( [68],n=27); automatically reinforced SIB [48,49] produced findings comparable that reported across smaller scale studies in body of literature as a whole.…”
Section: Sib Types Features and Sub-types Main Referencessupporting
confidence: 63%
“…A number of other studies which share features of what we define as a CCCS study have examined the outcomes of functional behavioral assessment procedures, including the analog FA conducted with inpatients (Hagopian et al, ), with outpatients (Kurtz et al, ), and with students (Mueller et al, ); and the interview‐informed synthesized contingency analysis (IISCA; Greer et al, 2019; Jessel et al, ; Slaton et al, ) . These methods have also been used to examine the outcomes associated with treatment procedures including FCT (Greer et al, ; Hagopian et al, ; Rooker et al, ) and NCR (Phillips et al, ). In addition to evaluating the general efficacy of assessment and treatment procedures, these methods have been used to examine the generality of procedures to specific populations, including preschool children with severe behavior (Kurtz et al, ), individuals with fragile X syndrome (Kurtz et al, ), and for specific problem behaviors (e.g., pica; Call et al, ).…”
Section: The Consecutive Controlled Case Series (Cccs)mentioning
confidence: 99%
“…Findings from CCCS studies can also help to build an empirical base for defining limits of the generality of the procedures. For example, Phillips et al () examined the general efficacy of NCR and defined some of its limits in what they termed a CCCS study of 27 cases (inpatients). They reported on the general efficacy of NCR across all cases and across functional classes of behavior.…”
Section: The Consecutive Controlled Case Series (Cccs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Such procedures could easily be adapted to applied research. Indeed, presenting tokens irrespective of behavior (such as the yoked‐control methods of Raiff et al, ) is a variant of a commonly used procedure in applied research—noncontingent reinforcement (NCR; Phillips, Iannaccone, Rooker, & Hagopian, ). Incorporating NCR‐like procedures as control procedures into token‐loss punishment programs will help reveal key behavioral functions of tokens.…”
Section: Functional Taxonomy Of Token Systemsmentioning
confidence: 99%